The pX region of the bovine leukemia virus is transcribed as a 2.1-kilobase mRNA. - Mamoun, R Z (1985)
The bovine leukemia virus mRNAs expressed in cultured bovine cells of various origins are a 9.0-kilobase genomic RNA, a 5.1-kilobase env RNA, and a newly detected 2.1-kilobase RNA corresponding to the transcription of pX sequences located in between the env gene and the 3' end of the provirus.